مدى تحقيق القيمة العادلة للمقاصد الشرعية في تحديد وعاء زكاة شركات الأموال - دراسة حالة البنك الإسلامي الفلسطيني - - بالرقي, تيجاني; بالنور, محمد الساسي (جامعة الوادي - University of Eloued, 2014)
This study aims at identifying the accounting measurement as stated in Islamic thought, and contemporary financial accounting thought, so the importance of this study stems from the presence of a clear trend among accounting thought theorists toward the preparation of the financial statements at fair value to measure accounting items, rather than the historical cost, and therefore there must be a kind of consideration of the compatibility of this trend with the basis of accounting measurement procedures when reporting on the financial position of the Islamic institutions. To achieve this objective, required data were collected through documents as a major tool of data collection. Moreover, this study was applied to Palestine Islamic Bank for fiscal year 2013, the study found that fair value provides a basis for reliable measurement in determining pot Bank Zakat, Which is endorsed by the Shariah Supervisory Board of the Bank, the World Bank study also recommended that separates more budget items that belong to the Zakat, and articulate way
the extent to acheive the fair value of shariah purposes in determination of the pot zakat funds companies study case on palestine islamic bank
مقال
Keywords: القيمة العادلة، وعاء زكاة شركات الأموال, القياس المحاسبي ، محاسبة زكاة شركات الأموال , البنك الإسلامي الفلسطيني.